2007
DOI: 10.3201/eid1311.070421
|View full text |Cite
|
Sign up to set email alerts
|

Danish Integrated Antimicrobial Resistance Monitoring and Research Program

Abstract: This program has led to changes in the use of antimicrobial agents in Denmark and other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 17 publications
1
90
0
1
Order By: Relevance
“…For both avoparcin and chloramphenicol, a ban was not effective in reducing the prevalence of resistance to the respective antimicrobial in pig isolates (2,9). This may be due to coselection by the continued use of other types of antimicrobials (1,15,16,33). Coselection by other antimicrobials, however, cannot explain the persistence of antimicrobial resistance for years after all use of antimicrobials was stopped, as documented in other studies of swine (13,25).…”
mentioning
confidence: 74%
“…For both avoparcin and chloramphenicol, a ban was not effective in reducing the prevalence of resistance to the respective antimicrobial in pig isolates (2,9). This may be due to coselection by the continued use of other types of antimicrobials (1,15,16,33). Coselection by other antimicrobials, however, cannot explain the persistence of antimicrobial resistance for years after all use of antimicrobials was stopped, as documented in other studies of swine (13,25).…”
mentioning
confidence: 74%
“…[7][8][9] The increase of antibiotic resistance following the use of antibiotics such as beta-lactams and growing the commensal and pathogenic ESBL (extended-spectrum beta-lactamase)-producing bacteria like E. coli strains especially in foodproducing animals pose a threat to the public health and food safety. [10][11][12][13][14] Researchers have suggested that the study of antibiotic resistance in commensal microorganisms like E. coli from the healthy animals would be quite useful, because they can be used as gnomon organisms to measure the prevalence of antibiotic resistance. These organisms could serve as a reservoir for the genes encoding antimicrobial resistance, which is transferred to the pathogenic bacteria or transmitted to the human by direct exposure to animals or via the food chain.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, only 706 new MRSA patients (colonization only or infection) were reported, which corresponds to 13/100,000 population (9). To maintain this status, Denmark has adopted a strict "Search and Destroy" policy, which includes active screening of at-risk persons at admission to a hospital (10).…”
mentioning
confidence: 99%